Islamic Resurgence and Western Reaction - Mohammad Akram Chaudhary (International Institute of Islamic Thought, 1994)
Islam is an ideology and a world religion with more than one billion adherents spread around the globe (Kettani 1986). I Muslims are a majority in more than forty-five countries from Africa to Southeast Asia. Their populations continue to grow, as do the Muslim populations in the former Soviet Union, China, India, Europe, and the United States. Islam seeks the evolution of a social structure based on the concept of the unity of mankind and comprised of individuals who are ·living moral and spiritual lives. It seeks to build a transnational society in which such narrow loyalties as color, race, and so on are negated, in which complete submission to the will of Allah is displayed, and in which Muhammad is the model to follow in daily affairs and is recognized as the chief interpreter of revelation. Denny (1993, 345) introduces Islam as "a vigorous, complex amalgam of peoples, movements, and goals, and not the monolithic, centrally coordinated, hostile enterprise that outsiders sometimes assume it to be." Muslim society is further characterized as having the capacity to resolve any changes, new situations or problems facing the ummah through the application of ijtihad. In the ever-changing sociocultural and socioeconomic conditions, it is ijtihad that prevents fossilization and precludes the development of stereotypes within Islam. With ijtihad, Islam has the inherent capacity to address and respond to change while still following the teachings of the Qur'an and the Prophet. Thus the term "fundamentalism," with its nonMuslim origin in early twentieth century Protestant Christianity, has no place in, and is therefore irrelevant to, the Islamic schema. This is not only because of the specifically Christian heritage and nature of the term, but also because of the derogatory and negative undertones that have been attached to it. The term "Islamic fundamentalism" is, in fact, an oxymoron, for one cannot be a Muslim if one does not adhere to the fundamentals of Islam. Denny (ibid., 345-46) writes: ...